2019
DOI: 10.1002/sce.21506
|View full text |Cite
|
Sign up to set email alerts
|

Toward a more humane genetics education: Learning about the social and quantitative complexities of human genetic variation research could reduce racial bias in adolescent and adult populations

Abstract: When people are exposed to information that leads them to overestimate the actual amount of genetic difference between racial groups, it can augment their racial biases. However, there is apparently no research that explores if the reverse is possible. Does teaching adolescents scientifically accurate information about genetic variation within and between US census races reduce their racial biases? We randomized 8th and 9th grade students (n = 166) into separate classrooms to learn for an entire week either ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(104 citation statements)
references
References 154 publications
(272 reference statements)
1
80
0
Order By: Relevance
“…People with higher pre-test genetic knowledge may also have other characteristics that contribute to the testing experience's reduction in essentialism such as openness to new ideas or stronger critical thinking. Yet, just as teaching adolescents scientifically accurate information about genetic variation between and within races can reduce their racial biases [59], increasing any test-takers' genetic knowledge may also help them put their test results in context. Such a finding might imply that educational materials or online genetics modules for future test-takers could help prevent these tests from advancing historically destructive views.…”
Section: Discussionmentioning
confidence: 99%
“…People with higher pre-test genetic knowledge may also have other characteristics that contribute to the testing experience's reduction in essentialism such as openness to new ideas or stronger critical thinking. Yet, just as teaching adolescents scientifically accurate information about genetic variation between and within races can reduce their racial biases [59], increasing any test-takers' genetic knowledge may also help them put their test results in context. Such a finding might imply that educational materials or online genetics modules for future test-takers could help prevent these tests from advancing historically destructive views.…”
Section: Discussionmentioning
confidence: 99%
“…As stated by Donovan (35), "when people are exposed to genetic explanations for group-based outcomes, it tends to strengthen a cognitive bias implicated in our reasoning about social categories," thus reinforcing the biological essentialism misconception. However, when students compare genetic variation within and between races, racial bias can be reduced (36). After critically analyzing the data around the "race is biological" misconception, students had an accurate understanding of the levels of between-and within-group genetic variation (35).…”
Section: Historical Contextmentioning
confidence: 99%
“…We take Donovan's words here as a directive when he wrote, "If repeated exposure to racial terminology in biology causes increases in bio-behavioral essentialism and prejudice because it leads students to perceive too much variation between races, then perhaps teaching students about the low amount of variation that actually exists across races will decrease racial bias. " With some colleagues, Donovan went on to test that hypothesis, and found that teaching students about genetic variation between U.S. census groupings significantly reduced their prejudice (Donovan et al 2019). In this light, it is encouraging to see professional organizations, such as the American Society of Human Genetics (ASHG) and the American Association of Physical (Biological) Anthropologists (AAP/BA), affirming their commitment to improve public genetic literacy in an effort to address misconceptions about genetics, ancestry, and "race", particularly how such knowledge is misused by white supremacist agendas (ASHG 2018; AAPA 2019).…”
Section: Biology Education "Race" and Racismmentioning
confidence: 99%